IMPLEMENTATION OF COMMUNITY DEVELOPMENT AND EMPOWERMENT AT PT PESONA KHATULISTIWA NUSANTARA - Imam Muazansyah; Irsyad Sudirman (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2020)
Research with a focus on Community Development and Empowerment in Mineral and Coal Mining Business Activities based on the Minister of Energy and Mineral Resources Regulation Number 41 of 2016 formulates 8 (eight) main programs from the PPM Master Plan (Community Development and Empowerment), namely programs in the fields of education, health, income or real work level, economic independence, socio-culture, environment, the formation of community institutions and infrastructure. Thank you to the Ministry of Research, Technology, and Higher Education of the Republic of Indonesia for funding this research through the Beginner Lecturer Research Grant (PDP) Contract Number 087/ SP2H/LT/DRPM/2020. In the Keputusan Menteri Energi dan Sumber Daya Mineral Nomor 1824K/30/MEM/2018, it explains the main points of the Guidelines for Preparation of Blueprints (Blue Print) and Guidelines for Preparation of the Master Plan for PPM. Minerba mining companies are required to carry out PPM throughout the cycle (exploration to post-mining) and are required to prepare a PPM Master Plan which is consulted and reported on its implementation to the Provincial Government and the Ministry of Energy and Mineral Resources. Provincial governments in areas that have a mining sector are required to prepare a PPM Blueprint and provide instructions to mining companies to prepare a PPM Master Plan. The output expected from this research is: Implement and find out the obstacles faced in the implementation of Community Development and Empowerment at PT Pesona Khatulistiwa Nusantara.